Meningkatkan Hasil Belajar Siswa Kelas VII SMP Darul Ulum 5 Rebalas Menggunakan Etnomatematika dengan Bahasa Madura - Dewi Ainiyah; Andika Setyo B.L; Ani Afifah (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This research aims to improve the mathematics learning outcomes of Grade VII B students at SMP Darul Ulum 5 Rebalas through the implementation of Madurese language-based ethnomathematics. The study is motivated by the students' difficulties in understanding mathematical concepts delivered in formal Indonesian, as their daily communication relies on the specific Madurese dialect of Rebalas Village. This study employs the Classroom Action Research (CAR) method using the Kemmis and McTaggart model, conducted in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The subjects of this research were 28 students from class VII B. The research instruments included test instruments in the form of group Student Worksheets (LKPD) and observation sheets for both teacher and student activities. The material focused on the topic of Lines and Angles. The results indicated an improvement in student learning outcomes from Cycle I to Cycle II. In Cycle I, the average group score was 80.2, which increased to 88 in Cycle II. Observations of student activities also showed a shift from passive participation in Cycle I to active and enthusiastic engagement in Cycle II. Furthermore, teacher observations showed significant improvement; initial issues regarding time management and excessive workloads were resolved, resulting in more enthusiastic and punctual teaching delivery. These findings demonstrate that the use of Madurese-based ethnomathematics helps students grasp mathematical terms more easily, increases discussion participation, and creates a more comfortable and interactive classroom atmosphere, thereby leading to improved learning outcomes.